Reproducibility of two electrical stimulation techniques to assess neuromuscular fatigue - Del Coso, J.; Hamouti,N.; Estevez, E.; Mora-Rodriguez, R. (European Journal of Sport Science, 2011)
The main aim of this study was to compare the reliability of percutaneous electrical stimulation over the muscle (MES) and electrical stimulation over the nerve (NES) to assess quadriceps muscle voluntary activation and muscle contractile properties. A secondary aim was to determine whether MES detects the fatigue induced by prolonged exercise in the heat. For the first purpose, eight participants performed on three non-consecutive days: quadriceps maximal voluntary contractions (MVC) with superimposed electrical stimulation to assess voluntary activation, and electrically evoked contractions to assess peak force (PEVO), using NES (ball-shaped cathode) or MES (adhesive electrodes). For the second purpose, the same participants pedalled for 2 h at 60% VO2max in a 36°C environment. Quadriceps maximal voluntary contractions, voluntary activation, and PEVO were measured before and just after the completion of exercise using MES. Voluntary activation assessed with MES presented lower intra-day (1.3±0.2 vs. 2.5±0.5%) and inter-day (1.7±0.3 vs. 2.9 ±0.4%) coefficients of variation than with NES. PEVO had lower intra-day and inter-day coefficients of variation (5.6±1.0 vs. 17.0±3.3%) and higher intraclass correlation values (ICC 0.95 vs. 0.85) when using MES than with NES either when stimulating at 20 or 80 Hz. Prolonged exercise in the heat reduced MVC (11±2%) and quadriceps muscle voluntary activation (5.2±0.5%) from pre-exercise values (P<0.05), as previously found. PEVO was unaffected by exercise in the heat. In conclusion, MES is more reliable than NES to assess quadriceps muscle voluntary activation and PEVO. In addition, MES readily detects the reduction in voluntary activation induced by prolonged exercise in the heat.